Stakeholders Mapping in The Implementation of Anti-Bullying Policies in the School Environment Lubuklinggau City - Anisa; Yogopriyatno, Jatmiko; Hardayani, Yorry (Indonesian Journal of Social Science Research, 2024)
The research aims to find the actors who play a role, their perceptions, and how patterns of interdependence work together in implementing anti-bullying policies in the school environment. The research framework adopted the concept of network governance related to actors, perceptions, and patterns of independence and roles in policy implementation. The research was conducted for six months using qualitative methods with 19 informants from regional apparatus organizations, task forces and public and private schools, parents and related organizations. Data were collected through FGDs, interviews, documentation and observation. Triangulation of sources and actors was conducted for data validity and reliability. Data analysis was conducted interactively through data display, reduction, and conclusion drawing. The results showed that the actors involved in reducing the stunting rate in Kaur Regency were identified as 19 actors from the government, semi-government, private sector, and social community The perception of actors related to the field of anti-bullying in the school environment generally regarding the context and content of anti-bullying policies in the school environment found a gap in the form of the reluctance / attitude of victims of bullying to report cases of bullying that occurred. The research recommends strengthening the participation model, increasing campaigns, building an information technology-based complaint system and open government data.